Empowering Youth in High-risk Areas: Assessing The Impact of a Psychospiritual Prevention Program on Drug Abuse Prevention - Amin Al Haadi Shafie; Dini Farhana Baharudin; Rafidah Aga Mohd Jaladin; Ahmad Najaa' Mokhtar; Khatijah Othman; Salleh Bin Amat; Suzaily Wahab; Anita Priantina; Nurhafizah Yassin; Mohd Azwan Fakhruddin Abd Halim (TELEMATIQUE, 2024)
Non-Indexed Publication